Plication versus Resection in Horizontal Strabismus Surgery - Kühne, Jill; Palmowski-Wolfe, Anja (Klinische Monatsblätter für Augenheilkunde, 2019)
Background To compare two commonly used strengthening procedures in strabismus surgery: plication and resection of the extraocular muscle (EOM).Patients and Methods From an anonymous databank of strabismus surgeries, performed at the University Eye Hospital Basel, patients with a horizontal strabismus surgery, consisting of a recession combined with either plication or resection of the antagonist and a follow-up of at least 3 months, were included. Exclusion criteria were previous eye surgeries, binocular surgeries, and simultaneous surgery of oblique or vertical EOM. Pre- and postoperative angles were measured using the alternating prism cover test during fixation at distance.Results Fifty-nine patients met the criteria and were matched according to the angle at baseline in the recession/plication group, resulting in 12 resection/recession and 12 plication/recession patients. There was no significant difference in the number of eso- and exodeviations, age at surgery, or gender between the groups. Mean difference between plication and resection was 1.2 PD at 1 week (p = 0.72) and 1.7 PD at 3 months (p = 0.61). A separate analysis for eso- and exodeviations showed no significant difference between recession/plication and recession/resection at 1 week or 3 months (p value side effect = 0.59; resection vs. plication at 1 week p = 0.68; resection vs. plication at 3 months: p = 0.57). The overall dose effect (SD) was 2.13 PD (0.88)/mm in the recession/plication group and 2.51 PD (0.81)/mm in the recession/resection group after 1 week (p = 0.331). After 3 months, the mean dose effect was 1.85 PD (1.06)/mm in the recession/plication group and 2.09 PD (1.12)/mm in the recession/resection group (p = 0.611).Discussion Our findings show that recession/plication is a valid alternative to recession/resection in horizontal strabismus without the need to cut the muscle, as we saw no difference in surgical effectiveness in either eso- or exodeviations at 1 week or at 3 months.
Keywords: plication; resection; strabisms; surgery